MANAGEMENT OF PARENTING ACTIVITIES IN PAUD IN MOTIVATING TO BE A WISE PARENT IN THE DIGITAL ERA - Nita Supartini; Arifah A. Riyanto; Kuswandy A. Marfu; Sri Nurhayati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The rapid progress of Information and Communication Technology (ICT) accompanied by easy access to social media, especially by minors who are easily exposed to information that has a negative impact on the character of children. Therefore, the involvement of parents is very helpful for teachers to carry out the process of educating children, especially educating children when at home (Parenting).Parenting really determines the growth and development of children's character according to the concept of "home education" ie the family is the best place to do education than other education centers and the first time children's education is given by parents which is carried out independently by utilizing the resources available in the family / environment (Dewantara , 1962).To provide information / insight into the new role of ICT in parenting activities in the digital age, a survey was conducted on parents of children under eight years old. The survey method uses a questionnaire distributed to parents of children. Survey data is analyzed / displayed using statistical diagrams.Survey data related to the use of ICT by parents / family are grouped into 4 main topics, namely data about parents, home / family environment data, family activity data and ICT data as child care tools.The survey findings that ICT has become a means of caring for the modern era but does not facilitate parenting parents and children demand more time with ICT. On the other hand, there are still many parents using books, toys, and TV in parenting activities for entertainment, educating, disciplining or valuing children. The second finding is that high intensity use of ICT by children is not a major concern of parents compared to concerns on health and education. The third finding is that most parents are of the opinion that ICTs cannot be used as an educational tool and are not harmful.